The Analysis of Local Culture in the Indonesian ELT Textbook for Junior High School - Rista Vanila; Sugeng Ariyanto; Bambang Suharjito (English Education Study Program, 2023)
This study aimed to analyze the representation of local culture in the government published ELT textbook for Junior High School student. Cultural diversity has become the issue related to the use of English that plays a great role to categorize English speakers and English varieties (Shin, Eslami and Chen, 2011). The integration of cultural values in ELT materials have been studied for years. Culture has become an important role in language teaching and learning, because it is believed that language cannot be taught to learners without its cultural elements. Textbook as one of the material that is highly used among English learners might represent the racial diversity and cultural background, therefore it is important to analyze how and what kind of cultural elements are being represented to the learners on the textbook.